Genome size is positively correlated with extinction risk in herbaceous angiosperms - Soto Gomez, Marybel; Brown, Matilda J M; Pironon, Samuel; Bureš, Petr; Verde Arregoitia, Luis D; Veselý, Pavel; Elliott, Tammy L; Zedek, František; Pellicer, Jaume; Forest, Félix; Nic Lughadha, Eimear; Leitch, Ilia J (The New phytologist, 2024)
Angiosperms with large genomes experience nuclear-, cellular-, and organism-level constraints that may limit their phenotypic plasticity and ecological niche, which could increase their risk of extinction. Therefore, we test the hypotheses that large-genomed species are more likely to be threatened with extinction than those with small genomes, and that the effect of genome size varies across three selected covariates: life form, endemism, and climatic zone. We collated genome size and extinction risk information for a representative sample of angiosperms comprising 3250 species, which we analyzed alongside life form, endemism, and climatic zone variables using a phylogenetic framework. Genome size is positively correlated with extinction risk, a pattern driven by a signal in herbaceous but not woody species, regardless of climate and endemism. The influence of genome size is stronger in endemic herbaceous species, but is relatively homogenous across different climates. Beyond its indirect link via endemism and climate, genome size is associated with extinction risk directly and significantly. Genome size may serve as a proxy for difficult-to-measure parameters associated with resilience and vulnerability in herbaceous angiosperms. Therefore, it merits further exploration as a useful biological attribute for understanding intrinsic extinction risk and augmenting plant conservation efforts.
Keywords: podnebí; IUCN Red List; genom rostlinný; C‐value; plant traits; Genome Size; conservation status; Genome, Plant; Climate; Phylogeny; fylogeneze; délka genomu; extinkce biologická; endemic species; nucleotype; Magnoliopsida; Extinction, Biological; life form